The Epistemological Import of Informed Consent in Clinical Research - Adenugba, Oluwaseun Adeola (Bangladesh Journal of Bioethics, 2013)
This paper attempts to establish the epistemological import and limits of informed consent in clinical research. It points out that informed consent is a necessary requirement in clinical research because it ensures adequate participation of care receivers in issues relating to their health. Besides ensuring that care receivers have knowledge of whatever medical intervention they are consenting to, informed consent, as an ideal, provides assurance that care receivers and others are neither coerced nor deceived. While the question of the value of informed consent in health care delivery is not so much controverted, in contest is the question of whether or not complete and wholly specifically informed consent can indeed be realized in medical intervention. Two orientations are identified in this debate. One insists that an individual will be able to make an informed decision and make reasonable choices amongst alternatives when fully informed. The other orientation sees as an epistemic illusion, achieving full informed consent, and rather opts for informed request. This paper examines this debate by clarifying the notion of informed consent, its components and its nexus with knowledge. The position of the paper is that informed consent is not only an ethical ideal in clinical research and health care; it is also an epistemic virtue that must be continuously strived towards. This paper establishes that health care receivers can only have an epistemic claim of their medical situation if all requirements of informed consent in health care delivery such as provision of adequate information, the risk and benefits of treatment, avoidance of vague/ambiguous statements, voluntariness, etc. are met. DOI: http://dx.doi.org/10.3329/bioethics.v4i2.16374 Bangladesh Journal of Bioethics 2013; 4(2) 34-40